Consumers’ Online Brand-Related Activities (COBRAS): A Systematic Review - Papasolomou, Ioanna; Melanthiou, Yioula; Vrontis, Demetris; Uzunboylu, Naziyet (My University, 2023)
Over the last decade, the COBRAs have attracted the attention of researchers in relation to their motives or outcome for the brand. However, the corpus of literature on COBRAs still is at a nascent stage and has created new opportunities pertaining to knowledge development. Undoubtedly, there is a clear need for some structure through mapping the research terrain to guide future research and further its development. Thus, a systematic review methodology was performed producing a top-quality pool of 35 papers that forge a robust understanding of this phenomenon. This research is the first study to perform a systematic review to examine the literature on COBRAs. Based on this, the findings contribute to theoretical knowledge, with extensive opportunities for generating novel theory and new forms of marketing practices.